Perancangan Pasar Rakyat Ampel Tipe A dengan Pendekatan Arsitektur Tropis di Kabupaten Boyolali, Jawa Tengah. - Tutie Rahayu; Sri Kurniasih; Anggraeni Dyah S. (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Ampel Market is one of the largest markets in Boyolali Regency. In 2004, the Ampel Market experienced a fire so that the market conditions until now have been irregular in the distribution of zoning, insufficient ventilation and natural lighting in buildings. The design of this Ampel Market will be upgraded to the Ampel Type A People's Market which is suitable for the area of ​​land, the number of traders and the location of the Ampel market. Tropical architecture is a type of style or concept in architectural design which is an answer and a form of adaptation of buildings to climatic conditions in a tropical area. Tropical climates are usually located near the equator and have special characteristics due to high solar heat, high humidity and rainfall, wind movement, and many other influences. Tropical architecture can provide answers to climate problems so that it can provide comfort and security in the market by utilizing natural resources. Keywords: Type A People's Market, Ampel Market, Tropical Architecture, Boyolali Regency.